Design and Etching of Bandpass FSS in Hard‑Coated Energy‑Saving Glass to Improve Transmission of Useful RF/MW Signals - Jahanzeb Khan, Jahanzeb Khan; Nafarizal Nayan, Nafarizal Nayan; Ghafer Iqbal Kiani, Ghafer Iqbal Kiani; Mohammed Abdullah Hussaini, Mohammed Abdullah Hussaini (Springer, 2023)
An efective etching method is proposed to create frequency-selective Surface (FSS) on energy-saving glass (ESG) for the improvement of RF/MW signals ranging from 0.5 GHz to 5 GHz. ESG is commonly used in buildings to reduce energy consumption, but the coating on it blocks frequencies from 0.5 GHz to 5 GHz, causing problems in communication systems. The unit cell of the proposed FSS design was modeled and simulated in CST Microwave Studio, and the results were verifed through experimental work. The results showed that the proposed design provided full transmission for the entire microwave band from 0.5 GHz to 5 GHz, including GSM, 3G, 4G, and personal communication signals. The proposed method involves etching the FSS pattern on ESG with a cutting width of 1 mm by using a glass cutter tool. The design is angle- and polarization-insensitive, as it provided angular stability from 0° to 45° oblique incidence for both transverse electric (TE) and transverse magnetic (TM) modes. Moreover, only 9.03% of the ESG coating was removed, which is acceptable in terms of heat loss compared to recent research. On average, there is an improvement of about 18 dB in attenuation for the entire band as compared to full coating. This method outperforms previous etching techniques, as full transmission is achieved for the entire band and not just for some specifc bands. Moreover, a complete sample of the ESG was etched and used in measurements instead of a small portion of the ESG as used by other researchers. The measured results are in good agreement with simulations. A stable frequency response under oblique incidence was achieved for both the TE and TM polarization.